Study of hypocalcemia and its risk factors in post thyroidectomy in Al-Karama Teaching Hospital - Surriah, Mohammed H.; Hassan, Ahmed N.; Bakkour, Amine M. (Journal of the Faculty of Medicine Baghdad, 2019)
Background: Hypocalcemia is a well-recognized complication of thyroid surgery. The aim of this study was to determine the incidence of hypocalcemia after thyroid surgery and find out the risk factors involved regarding the patient’s age, gender, muscular build, clinical diagnosis, extent of surgery, ligation of the inferior thyroid artery, and pathology report. Patients and Methods: This case series study was carried out on 50 patients who have undergone thyroid surgery for various thyroid diseases at the surgical department of Al-Karama Teaching Hospital for the period between January 2016 and July 2017. Serial serum calcium measurements were recorded as well as details of the operation, patient’s age and gender, whether or not inferior thyroid artery was ligated, and the pathological report. Hypocalcemia was considered transient if it resolved within 6 months and permanent if it persisted after 6 months and the patient was maintained on supplementation therapy of calcium and vitamin D. Results: The study found that the incidence of post-thyroidectomy hypocalcemia was 30% and in the majority of the cases (24%) was transient, while it was permanent in only (6%) of the cases; and had occurred mainly after total thyroidectomy and in cases with ligation of the inferior thyroid artery. Conclusions: It was concluded that post thyroidectomy hypocalcemia is a relatively common complication but it is transient in the majority of the patients. Its incidence is related to the extent of the surgery and can be reduced by the good preparation of the patient preoperatively.